Epidemiology and antifungal susceptibility patterns of Candida isolates from Greek women with vulvovaginal candidiasis. Issue 8 (12th June 2019) - Maraki, Sofia; Mavromanolaki, Viktoria Eirini; Stafylaki, Dimitra; Nioti, Eleni; Hamilos, George; Kasimati, Anna
Summary: Vulvovaginal candidiasis (VVC) is a common infection of the genital tract affecting millions of women worldwide. Data on epidemiological trends of VVC in Greece are scarce. This study was undertaken to evaluate the prevalence of VVC among symptomatic women in Crete, Greece, identify the Candida species involved and determine their susceptibility to antifungals. Over a 6‐year period (2012‐2017), 10 256 symptomatic women with vaginitis were evaluated. Isolation of yeasts was performed on Sabouraud dextrose agar with chloramphenicol, and the isolates were identified using the API 20 C AUX and/or the Vitek 2 YST card. Susceptibility of the isolates to amphotericin, fluconazole, voriconazole and flucytosine was determined by the Vitek 2 automated system. The results were interpreted according to Clinical and Laboratory Standards criteria. Vaginal swab cultures of 1217 (11.9%) women yielded Candida species. Recurrent VVC was documented in 62 (5.1%) of them. Candida albicans was the most frequently isolated species (75.6%), followed by Candida glabrata (13.6%). Overall, resistance rates to amphotericin B, fluconazole, voriconazole and flucytosine were 0.2%, 6.6%, 1.4% and 2.1%, respectively. Fluconazole resistance of C. albicans significantly increased in the second period of the study (2015‐2017) ( P = 0.031). This study demonstrated that VVC is a common infection among women in our region, with C. albicans being the predominant species involved. Although resistance to antifungals was infrequent, resistance to fluconazole among C. albicans isolates was found to significantly increase with time. Continued surveillance of changes in species distribution and susceptibility to antifungals are necessary to guide treatment.